Bites by the noble false widow spider Steatoda nobilis can induce Latrodectus-like symptoms and vector-borne bacterial infections with implications for public health: a case series. (2nd January 2022) - Dunbar, John P.; Vitkauskaite, Aiste; O'Keeffe, Derek T.; Fort, Antoine; Sulpice, Ronan; Dugon, Michel M.
Abstract: Context: In recent years, the Noble false widow spider Steatoda nobilis (Thorell, 1875) has expanded its range globally and may represent a potential threat to native ecosystems and public health. Increasing numbers in synanthropic habitats have led to more human encounters and envenomations. Steatoda nobilis bites were previously classed as medically significant with similarities to bites from true black widows of the genus Latrodectus but deemed milder in onset, with symptoms generally ranging from mild to moderate. Case details: In this manuscript we present 16 new cases of S. nobilis envenomations bringing the total number of confirmed cases reported in the literature to 24. We report new symptoms and provide discussion on the contributing factors to pathology following bites by S. nobilis . Discussion: We report a range of pathologies including necrosis, Latrodectus -like envenomation symptoms that include debilitating pain, tremors, fatigue, nausea, hypotension, and vectored bacterial infections including cellulitis and dermatitis. Symptoms ranged from mild to severe, requiring hospitalisation in some cases.